Investigation on crystal growth characterisation and molecular docking insights of 8-hydroxyquinoline. (2021) - Kavitha, T.; Aruna Priyankaa, B.K.; Yuvarani, N.; Sudha, N.; Inmozhi, C.; Mathammal, R.
Abstract: Organic single crystal of 8-Hydroxyquinoline (8HQ) having good optical quality has been grown by slow evaporation solution growth technique using acetone as solvent. The cell parameters of the grown crystal were found by Single X-ray diffraction and they belong to monoclinic system with space group P 21/ n . The optical property of the grown crystals was identified using UV–Visible spectrum. The functional groups present in the title molecule were identified with the aid of FTIR spectrum. The electronic structure of materials is examined by using Photoluminescence spectroscopic technique. The structure is optimized using basis set [B3LYP/6-31+G(d, p)] using Density Functional Theory (DFT). The optimized structure is used to determine vibrational assignment, UV spectra, HOMO-LUMO, Molecular Electrostatic Potential etc. Generally, quinolone derivatives are well known to possess rich diversity of biological properties and hence the molecular docking analysis of 8HQ has been validated for an antimalarial target 5TBO.